Literacy Padepokan "Iqra": Awakening the Ta'awun Spirit in the Ecological Literacy Movement in Gampingan Village, Pakuncen Village, Wirobrajan District, Yogyakarta City - Tanto Lailam; Nita Andrianti (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
The literacy movement by arousing the spirit of ta'awun in ecology is a community service that aims to build a good understanding of ecology, ecological culture, and ecological awareness in Gampingan village. The community service method is carried out by conducting ecological literacy training, counseling, mentoring, and facilitation. Several activities were carried out together (all partners), starting from strengthening the understanding of ecological literacy theory through literacy training and book references. Also, counseling is to increase legal awareness and environmental awareness in the community (ecological awareness). Increasing the understanding of ecological literacy is also carried out by building the "Padepokan Literasi Iqro" as a place to read, write, discuss, and a space to solve ecological problems in Kampung Gampingan.